Body-worn cameras to prevent workplace aggression among ticket inspectors: Protocol for a randomized controlled trial - Camilla Bank Friis; Merlin Schaeffer; Juliane Starcke Neergaard; Lasse Suonperä Liebst (PLoS ONE, 2026)
Background Service and frontline personnel are among the occupational groups with the highest rates of workplace aggression. To address the risk of victimization, various preventive measures have been introduced, with body-worn cameras increasingly adopted. However, evidence of their effectiveness remains inconclusive, with existing studies heavily concentrated in U.S. policing contexts, limiting the generalizability of findings across settings. This study aims to strengthen the evidence base through a randomized controlled trial testing the preventive effect of body-worn cameras among ticket inspectors in Denmark. Methods The trial will involve approximately 60 inspectors employed by three Danish public transport companies. Randomization will occur at the shift level, yielding approximately 3,000 shifts in total. The main analysis compares wearing a camera versus not wearing a camera, pooling data from all three companies. A secondary analysis, restricted to two companies, additionally tests whether a visible badge notifying passengers of potential recording strengthens any preventive effect. In parallel, field observations of inspection workdays will be conducted to gain in-depth insights into how and why cameras may influence interactions. Discussion This study presents a rare randomized controlled trial on the preventive effect of body-worn cameras against workplace aggression outside a U.S. policing context. If the hypothesis of a preventive effect is confirmed, the findings will have direct practical implications for deploying this technology to reduce workplace aggression.